BiVO4/TiO2(N2) Nanotubes Heterojunction Photoanode for Highly Efficient Photoelectrocatalytic Applications - Wang, Rui; Bai, Jing; Li, Yunpo; Zeng, Qingyi; Li, Jinhua; Zhou, Baoxue (Nano-Micro Letters, 2016)
We report the development of a novel visible response BiVO4/TiO2(N2) nanotubes photoanode for photoelectrocatalytic applications. The nitrogen-treated TiO2 nanotube shows a high carrier concentration rate, thus resulting in a high efficient charge transportation and low electron–hole recombination in the TiO2–BiVO4. Therefore, the BiVO4/TiO2(N2) NTs photoanode enabled with a significantly enhanced photocurrent of 2.73 mA cm−2 (at 1 V vs. Ag/AgCl) and a degradation efficiency in the oxidation of dyes under visible light. Field emission scanning electron microscopy, X-ray diffractometry, energy-dispersive X-ray spectrometer, and UV–Vis absorption spectrum were conducted to characterize the photoanode and demonstrated the presence of both metal oxides as a junction composite.